Safe dispensing practice: development and evaluation of a blended learning tool to enhance dispensing in pharmacy practice education - Hope, D.; Hattingh, H. Laetitia; Haywood, A. (International Association of Technology, Education and Development (IATED), 2011)
Prescription dispensing is one of the core functions of a pharmacist. It is a complex process that involves a range of cognitive and manual steps. Ideally, pharmacy students first need to perform basic dispensing data processing functions before proceeding to more complicated clinical interpretation functions. From a training perspective, it is therefore important to introduce the various steps to pharmacy students in a sequential and systematic way. The aim of this project was to develop a blended learning tool to be utilised by pharmacy students over consecutive years of their program and to evaluate the impact of the tool on students’ knowledge, understanding and application of the dispensing process